2002
DOI: 10.1523/jneurosci.22-07-02718.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Alterations of Specific Metabolic Pathways in Schizophrenia

Abstract: Dysfunction of the dorsal prefrontal cortex (PFC) in schizophrenia may be associated with alterations in the regulation of brain metabolism. To determine whether abnormal expression of genes encoding proteins involved in cellular metabolism contributes to this dysfunction, we used cDNA microarrays to perform gene expression profiling of all major metabolic pathways in postmortem samples of PFC area 9 from 10 subjects with schizophrenia and 10 matched control subjects. Genes comprising 71 metabolic pathways wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
224
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 406 publications
(258 citation statements)
references
References 55 publications
25
224
1
6
Order By: Relevance
“…A number of genes functioning in polyamine metabolism have also been implicated in schizophrenia through microarray analysis. 24 Polyamines themselves (primarily spermine but also spermidine) are known to modulate the activity of AMPA and NMDA subtype glutamate receptors. 25,26 Putrescine can be converted to GABA through an acetylated intermediate while glutamate is capable of modification to ornithine, the precursor of putrescine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of genes functioning in polyamine metabolism have also been implicated in schizophrenia through microarray analysis. 24 Polyamines themselves (primarily spermine but also spermidine) are known to modulate the activity of AMPA and NMDA subtype glutamate receptors. 25,26 Putrescine can be converted to GABA through an acetylated intermediate while glutamate is capable of modification to ornithine, the precursor of putrescine.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of genes for validation was carried out on the basis of their involvement in stress response, neurodevelopment, connection to neurotransmitter pathways implicated in major depression and on the significance of findings from microarray analysis. 24.676.7 (SMD), F = 1.060, P = 0.357). There was no correlation between PMI and tissue pH within the PMI range of microarray study samples.…”
Section: Real-time Pcrmentioning
confidence: 93%
“…Studies of patients with schizophrenia have used microarray to screen cortical (DLPFC, superior temporal gyrus, and entorhinal cortex) and cerebellar samples from a matched set of subject to determine genes that are differentially expressed (3)(4)(5)(6)(7)(8)(9)(10)(11). Broadly, these reports to date have suggested alterations in functional pathways involving myelin, synaptic, metabolic, and proteasome-ubiquitin related processes in schizophrenia, though the specific differences, their magnitude and directionality, have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…These microarray comparisons used pools of RNA representing 20 patients and 20 controls. Another recent microarray study (6) reported that expression of the metabolic enzyme cytosolic malate dehydrogenase (MDH1) was decreased in the DLPFC of patients with schizophrenia, whereas another report showed the opposite (4). Neuroleptic treatment of monkeys increased MDH1 in the DLPFC (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation